S100A6 Regulates Endothelial Cell Cycle Progression by Attenuating Antiproliferative Signal Transducers and Activators of Transcription 1 Signaling. Issue 9 (September 2016) - Lerchenmüller, Carolin; Heißenberg, Julian; Damilano, Federico; Bezzeridis, Vassilios J.; Krämer, Isabel; Bochaton-Piallat, Marie-Luce; Hirschberg, Kristóf; Busch, Martin; Katus, Hugo A.; Peppel, Karsten; Rosenzweig, Anthony; Busch, Hauke; et al.
Abstract : Objective—: S100A6, a member of the S100 protein family, has been described as relevant for cell cycle entry and progression in endothelial cells. The molecular mechanism conferring S100A6's proliferative actions, however, remained elusive. Approach and Results—: Originating from the clinically relevant observation of enhanced S100A6 protein expression in proliferating endothelial cells in remodeling coronary and carotid arteries, our study unveiled S100A6 as a suppressor of antiproliferative signal transducers and activators of transcription 1 signaling. Discovery of the molecular liaison was enabled by combining gene expression time series analysis with bioinformatic pathway modeling in S100A6-silenced human endothelial cells stimulated with vascular endothelial growth factor A. This unbiased approach led to successful identification and experimental validation of interferon-inducible transmembrane protein 1 and protein inhibitors of activated signal transducers and activators of transcription as key components of the link between S100A6 and signal transducers and activators of transcription 1. Conclusions—: Given the important role of coordinated endothelial cell cycle activity for integrity and reconstitution of the inner lining of arterial blood vessels in health and disease, signal transducers and activators of transcription 1 suppression by S100A6 may represent a promising therapeutic target to facilitate reendothelialization in damaged vessels. Abstract : Supplemental Digital Content is available in the text.